2023
DOI: 10.1128/spectrum.02805-22
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relevance between Gut Microbiota-Metabolites Profile and Chronic Kidney Disease with Distinct Pathogenic Factor

Abstract: Gut dysbiosis-altered metabolite association exhibits specific and convincing utility to differentiate CKD associated with distinct pathogenic factor. These results present the validity of pathogenesis-associated markers across healthy participants and high-risk population toward the early screening, prevention, diagnosis, or personalized treatment of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…and Lactobacillus spp. were also found able to correlate more precisely with L-Proline and Stearic acid were found able to differentiate diabetic nephropathy patients from healthy participants ( Chen et al, 2023 ).…”
Section: Microbiological Characteristics Of the Gut In Diabetic Nephr...mentioning
confidence: 97%
“…and Lactobacillus spp. were also found able to correlate more precisely with L-Proline and Stearic acid were found able to differentiate diabetic nephropathy patients from healthy participants ( Chen et al, 2023 ).…”
Section: Microbiological Characteristics Of the Gut In Diabetic Nephr...mentioning
confidence: 97%
“…High levels of L-leucine and isoleucine are significantly correlated with rapid estimated GFR decline. Compared with healthy controls, DN patients have elevated levels of stearic acid, glutaric acid, 2-Amino-3-methylimidazo(4,5-f) quinoline, and L-proline, and decreased levels of 1,3,7-trimethyluric acid, homocarnosine, epinephrine, N-acetylputrescine, linoleic acid, and ephedrine ( Chen et al., 2023 ). In addition, the abundance of SCFA metabolites, valerate, and caproate, are significantly decreased in the serum of DN patients ( Zhong et al., 2022 ).…”
Section: Microbial Metabolites In Dn Patientsmentioning
confidence: 99%
“…The human intestine harbors a variety of microorganisms, such as bacteria, fungi, and viruses, that are involved in the digestion of food, synthesis of essential vitamins and amino acids, elimination of pathogens, and clearance of toxins ( Fernandes et al., 2022 ; Xiang et al., 2023 ). Through metagenomic sequencing analysis of human fecal samples, intestinal flora such as Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, Verrucomicrobia, Cyanobacteria, and Spirochaetes have been identified ( de Vos et al., 2022 ; Chen et al., 2023 ). Many studies have shown that changes in the abundance, diversity, and colonization location of the gut microbiota and alterations in serum metabolites can lead to DN, diabetic retinopathy, diabetic cardiovascular disease, and other complications ( Lv et al., 2022 ; Xu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis is an imbalance or perturbation in the GMs composition that results in a proliferation of harmful bacteria like Enterobacteriaceae or a reduction in beneficial bacteria like Bifidobacterium and Lactobacillus [ 14 ]. For individuals dealing with ongoing kidney conditions, such as chronic kidney disease (CKD) and terminal kidney failure, often referred to as end-stage kidney disease (ESKD), the harmonious and mutually advantageous connection is disrupted, leading to an imbalance known as dysbiosis [ 15 ]. The consequences of this dysbiosis go beyond the gut and impact the kidneys via the so-called gut–kidney axis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%